Perancangan pet furniture ramah anak untuk meningkatkan interaksi antara anak dan hewan peliharaan - Jeanny Octavia; Yusita Kusumarini (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Living organisms basically live together, no exception for humans and animals. Therefore, the welfare of humans and animals need to be considered. One of many ways is to domesticate and tame it, turning some animals into pets, so we can interact with each other. Interaction can be done by anyone, even by children in their early childhood, as at this age, children learn to understand the surrounding environment, including the pets in their homes. The purpose of this design is to provide innovation of facilities to support the interaction of children and pets in the form of child-friendly pet furniture. These pet furnitures not only provide sleeping facilities for pets, but also provide entertaining facilities for pets and children so they will be able to interact. The method to create the design is by using design thinking. The method is divided into 5 stages, namely emphatize, define, ideate, prototype, and test. The final result of the design are 3 products of design ideas, which are made differently based on the types of pets and children’s activities. Each product design ideas have the same design limitations, including dog breed, the age of the child, and the placement of the product.